Host Regulators of Liver Fibrosis During Human Schistosomiasis - Kamdem, Severin Donald; Moyou-Somo, Roger; Brombacher, Frank; Nono, Justin Komguep (Frontiers in Immunology, 2018)
Liver fibrosis is a wound-healing process purposely aimed at restoring organ integrity after severe injury caused by autoimmune reactions, mechanical stress or infections. The uncontrolled solicitation of this process is pathogenic and a pathognomonic feature of diseases like hepatosplenic Schistosomiasis where exacerbated liver fibrosis is centrally positioned among the drivers of the disease morbidity and mortality. Intriguingly, however, liver fibrosis occurs and progresses dissimilarly in schistosomiasis-diseased individuals with the same egg burden and biosocial features including age, duration of residence in the endemic site and gender. This suggests that parasite-independent and currently poorly defined host intrinsic factors might play a defining role in the regulation of liver fibrosis, the hallmark of morbidity, during schistosomiasis. In this review, we therefore provide a comprehensive overview of all known host candidate regulators of liver fibrosis reported in the context of human schistosomiasis.